Sequential Solid-State and Submerged Fermentation to Increase Yarrowia lipolytica Lipase Production from Palm Oil Production Chain By-Products - Camila P. L. Souza; Adejanildo da S. Pereira; Érika C. G. Aguieiras; Priscilla F. F. Amaral (Fermentation)
This study investigates the potential of sequential solid-state and submerged fermentation (SeqF) to enhance lipase production by Yarrowia lipolytica using by-products from the palm oil production chain. Palm fiber and palm oil deodorizer distillate (PODD) were utilized as substrates in both fermentation stages. Solid-state fermentation (SSF) yielded significant lipase activity when palm fiber was used alone (1.55 U/g in 48 h), while submerged fermentation (SmF) showed improved enzymatic production with the combination of fiber and PODD (1171 U/L in 72 h). The integration of SSF and SmF in SeqF achieved superior lipase activities, reaching 4464.5 U/L, an 8.3-fold increase compared to SmF alone, in Erlenmeyer flasks. SeqF-lyophilized biocatalysts from Erlenmeyer experiments showed better hydrolytic activity (131 U/g) when the best conditions were reproduced in a 4 L bioreactor (33 U/g). The SeqF-lyophilized biocatalyst was employed in esterification reactions to synthesize mono- and diacylglycerols, achieving a 24.3% conversion rate. The study highlights SeqF as a promising and sustainable approach for valorizing agro-industrial residues, contributing to biocatalyst production and advancing circular bioeconomy initiatives.